Can group identity explain the gender gap in the recruitment process? - Igor Asanov; Maria Mavlikeeva (Industrial Relations Journal, 2022)
Despite evidence that the gender gap in the labour market favours men, aggregate findings from correspondence studies show that women are more likely than men to be invited for a job interview. We hypothesize that the predominance of women among recruiters may explain this somewhat puzzling finding; recruiters may favour applicants of their own gender. We use the data from a large-scale correspondence study to test this hypothesis. As expected, we find that female applicants are more likely to receive callbacks for interview. We also see that in our sample the majority of contact persons responsible for the recruitment process are female. More importantly, we find that if recruiter and applicant are of the same gender, then the likelihood that the applicant will be invited for an interview increases. These findings reveal the gender favouritism at the selection stage in the labour market.
Keywords: 330